Experimental and Numerical Investigation of Liquid Storage Tanks Under Seismic Excitation - Bahreini Toussi, Iman (Université d'Ottawa / University of Ottawa, 2016)
Liquid storage tanks are a crucial type of structures. They are used to store various types of liquids and liquefied gases in different situations. In seismic regions, functionality of these structures after severe earthquakes is an important factor in their design. In earthquake-prone regions, the sloshing phenomena has an important role in the design procedure. Current design codes and guidelines (e.g. ACI 350.3 and ASCE 7) are based on analytical studies that in some cases can be inaccurate in prediction of forces and pressures. Since a long time ago scientists have studied the sloshing phenomena in liquid storage tanks with different methods including analytical, numerical and experimental studies. In the current study, rectangular ground-supported tanks are studied and the effect of seismic loading on them is investigated both experimentally and numerically. For the experimental tests, the tanks were placed on a shaking table and using high-speed HD cameras, tests were filmed and later analyzed frame by frame to capture the critical moments. To investigate the bi-lateral effect of base excitation on the tanks, they were oriented on the table with four different angles. In the numerical study, a computational fluid dynamics tool - OpenFOAM - was used to simulate the tank motion and finally the results were compared with the experiment in order to develop a reliable model.
Keywords: Liquid Storage Tanks; Earthquake; Seismic; Numerical; Experimental; OpenFOAM